Assessing the impact of the use of information and communication technologies in the agricultural sector in Africa : the case of mobile telephony - (:unkn) unknown (My University, 2020)
The objective of this thesis is to capture the potential of information and communication technologies (ICTs), specifically mobile phones in Africa to alleviate the living conditions and empower households in rural areas, particularly in Sub-SaharaAfrica through information dissemination, rent redistribution, and financial inclusiveness. As the last developed continent, Africa suffers from poverty, lack of essential infrastructure, famine problems, the highest illiteracy rates, and limited access to financial services, so International organizations such as the World Bank argues that the expansion of mobile telephony adoption represents an opportunity to overcome some of Africa’s obstacles through innovative uses in the rural world, which suffers more from physical barriers. We focus on assessing the impact of the innovative uses of mobile phone services in the agricultural sector where I will draw conclusions on mobile phone services’ benefits, quantify them, and advise public and private authorities and organizations to set up suitable services to the populations’ needs.
Keywords: African Research